THE INFLUENCE OF DIGITAL MARKETING, SERVICE PERCEPTIONS, CUSTOMER COMMENTS ON CUSTOMER SATISFACTION USERS OF THE SHOPEE APPLICATION IN MEDAN CITY - Ira Junita Br Hutapea; Hendra Jonathan Sibarani; Julius Tambunan; Yusni Agrawa Pasaribu (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
This research was conducted to analyze and develop the influence of digital marketing, service perception, and customer comments on the assessment of customer satisfaction in using the Shopee application. This study was done in the area of Medan Helvetia in the city of Medan. This research employs a quantitative method. The study population is comprised of 164.910 residents of the Medan Helvetia subdistrict. The approach of estimating the sample size using the Slovin formula yielded 100 respondents with a 10% error. Techniques for data collection via the use of research questionnaires Validity and reliability analysis, statistical descriptive analysis, respondent explanation analysis, classical assumption analysis, linear regression analysis, and coefficient of determination analysis were all employed to analyze the data. Tests based on data processing show that digital marketing, service perceptions, and customer comments all have a positive effect on customer satisfaction